Dynamics of neon ions after neon gas seeding into tokamak plasma. (27th September 2019) - Bisai, N.; Chowdhuri, M.B.; Banerjee, S.; Raj, Harshita; Dey, Ritu; Tanna, R.L.; Manchanda, R.; Jadeja, K.A.; Ghosh, J.
Abstract: Two dimensional interchange turbulence has been used to describe neon gas interaction with tokamak plasma, and is able to include anomalous transport effects self-consistently in the edge and scrape-off layer (SOL) regions. Model equations related to the plasma turbulence coupled with neon gas have been solved numerically using the BOUT++ framework code. Two different fluid models of the neon gas have been investigated, and in this context a few results related to the Aditya tokamak are presented. Numerical results indicate that ionization and radiative cooling processes modify the plasma turbulence. The existence of neon ions and their radial profile in the edge and SOL regions are the most significant results in this work. This new result has been investigated in detail in the presence of the interchange plasma turbulence. Other relevant results such as an increase of plasma density and a small change of electron temperature are also presented. In turbulence saturated states the electron temperature can increase slightly even in the presence of radiative cooling. Neon ions in the presence of polarization drift and radiative cooling modify the radial electric field and its radial shear. Radial electron energy flux has been investigated in the context of poloidal velocity shear and turbulence decorrelation rates. An increase of the electron energy confinement time has been observed numerically, mainly in the SOL region in the presence of gas seeding. Experimental results show an increase of global energy confinement time only when the gas seeding becomes effective in changing the global plasma parameters.